2019
DOI: 10.1111/and.13363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between microsurgical varicocelectomy with and without testicular delivery for treatment of varicocele: A systematic review and meta‐analysis

Abstract: The present study was conducted to assess the semen parameters, complications and clinical effect of microsurgical varicocelectomy with testicular delivery (TD) for treatment of varicocele. Relevant studies were collected and reviewed systemically from PubMed, Medline, Embase, Web of Science, China National Knowledge Infrastructure databases and the Cochrane Library and a meta‐analysis was performed. Relative ratio (RR), standardised mean difference (SMD) and their 95% confidence intervals (CIs) were adopted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…A detailed statistical method of meta‐analysis was stated in our previous study (Song, Lu, Xu, Yang, & Liu, ). Weighted mean difference (WMD), standard mean difference (SMD) and their 95% confidence interval (CI) were calculated for outcomes and statistical significance of WMD or SMD was due to the Z test.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed statistical method of meta‐analysis was stated in our previous study (Song, Lu, Xu, Yang, & Liu, ). Weighted mean difference (WMD), standard mean difference (SMD) and their 95% confidence interval (CI) were calculated for outcomes and statistical significance of WMD or SMD was due to the Z test.…”
Section: Methodsmentioning
confidence: 99%
“…However, Allameh et al (2018) found that MSV with testicular delivery could improve the sperm motility and per cent of normal morphology compared with that without testicular delivery. In a meta‐analysis published recently, it is found that MSV with testicular delivery could increase total sperm count in patients with grade II and III varicocele, while taking no benefits to sperm viability, sperm concentration and progressively motile spermatozoa (Song, Lu, Xu, Yang, & Liu, 2019). And the results also indicated that MSV with testicular delivery caused a higher incidence of orchiepididymitis and scrotaloedema and took longer operation time compared with MSV without.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular delivery is needed if the gubernacular veins are ligated, which not only requires an enlarged incision (which increases the difficulty of the local anesthesia and the risk of testicular injury) but also may result in impaired venous return and scrotal edema, along with an increased incidence of hydrocele (25,26). A meta-analysis in 2019 revealed that ligation of the gubernacular veins resulted in a higher incidence of orchiepididymitis (RR =4.36; 95% CI: 1.12-16.99; P=0.034) and scrotal oedema (RR =4.25; 95% CI: 2.40-7.54; P<0.001) and showed no beneficial influences on semen parameters or natural conception (27). In addition, whether the gubernacular veins were handled or not did not have any effect on the VC recurrence rate (28).…”
Section: Complicationsmentioning
confidence: 99%